2012
DOI: 10.3109/13880209.2012.666253
|View full text |Cite
|
Sign up to set email alerts
|

Prosopis cineraria: A potential nootropic agent

Abstract: The extract exerted significant nootropic activity in the MWM test which may be attributed to the inhibition of brain AChE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Results of total phenolic and flavonoidal content in current study also indicated their abundant existence in PC. Nootropic activity of methanolic extract of PC bark possesses antioxidant and AChE inhibition activity due to phenolic compounds ( Bithu et al, 2012 ). Our study shows BuPC have the highest potential for antioxidant and AChE inhibitory activity evaluated by in vitro DPPH assay and Ellman’s method, respectively, as compared to other fractions, which might be associated with the presence of rich amount of phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of total phenolic and flavonoidal content in current study also indicated their abundant existence in PC. Nootropic activity of methanolic extract of PC bark possesses antioxidant and AChE inhibition activity due to phenolic compounds ( Bithu et al, 2012 ). Our study shows BuPC have the highest potential for antioxidant and AChE inhibitory activity evaluated by in vitro DPPH assay and Ellman’s method, respectively, as compared to other fractions, which might be associated with the presence of rich amount of phenolic and flavonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding oral toxicity study, Bithu et al (2012) reported the safety of PC up to 2000 mg/kg, as there was no mortality and signs of toxicity in mice was observed by examining their behavioral status, such as convulsions, salivation, diarrhea, lacrimation and feeding behavior. No adverse effect was observed in vital organs, i.e., stomach, pancreas, eye and prostate gland, upto 31.5 mg/kg p.o.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…due to presence of various primary and secondary metabolites. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] There is no pharmacognostic data available on quantitation of urosolic acid and lupeol with respect to P. cineraria leaves to determine the physicochemical standards required for the future benefit of the crude drug. Urosolic acid and lupeol are the responsible for many of the pharmacological activities of this plant, so the main aim of the present investigation was to study the macroscopic, microscopic, physicochemical standards, antioxidant properties of this species.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of various primary and secondary metabolites. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] There is a lack of scientific data on the proteins of this species and there analytical, antimicrobial and antioxidant activities. Hence, the present study was undertaken to assess the phytochemical content and screening the proteins for their microbiological and antioxidant properties as per WHO and standard guidelines.…”
Section: Introductionmentioning
confidence: 99%